3-Hydroxypropionaldehyde production from crude glycerol by Lactobacillus diolivorans with enhanced glycerol uptake - Katharina Anna Lindlbauer; Hans Marx; Michael Sauer (Biotechnology for Biofuels, 2017)
Abstract Background In their quest for sustainable development and effective management of greenhouse gas emissions, our societies pursue a shift away from fossil-based resources towards renewable resources. With 95% of our current transportation energy being petroleum based, the application of alternative, carbon-neutral products—among them biodiesel—is inevitable. In order to enhance the cost structure of biodiesel biorefineries, the valorization of the crude glycerol waste stream into high-value platform chemicals is of major importance. Results The purpose of this study is the production of 3-hydroxypropionaldehyde (3-HPA) from biodiesel-derived crude glycerol by Lactobacillus diolivorans. Particular focus is given on overcoming potential limitations of glycerol transport into the cell, in order to use the cells’ total glycerol dehydratase capability towards the formation of 3-HPA as the main product. Recombinant overexpression of the endogenous glycerol uptake facilitating protein PduF results in a significant increase of glycerol conversion by a factor of 1.3. Concomitantly, glycerol dehydratase activity increased from initially 1.70 ± 0.03 U/mg protein to 2.23 ± 0.11 U/mg protein. With this approach, an average productivity of 4.8 g3-HPA/(gCDM h) yielding up to 35.9 g/L 3-HPA and 0.91 mol3-HPA/molGlycerol have been obtained. Conclusion Lactobacillus diolivorans proves to be a valuable cell factory for the utilization of crude glycerol delivering high-value C3 chemicals like 3-HPA, 1,3-propanediol (1,3-PDO) and 3-hydroxypropionic acid (3-HP). Enhancing the glycerol influx into the cell by genetic engineering was successful paving the way towards the commercial production of 3-HPA.